An Anatomic Study of the Percutaneous Endoscopically Assisted Calcaneal Osteotomy Technique to Correct Hindfoot Malalignment. (February 2017) - Veljkovic, Andrea; Tennant, Joshua; Rungprai, Chamnanni; Abbas, Kaniza Zahra; Phisitkul, Phinit
Background: Open calcaneal osteotomy using traditional methods is associated with complications such as sural nerve injury and potential wound healing problems. We hypothesized that by using novel minimally invasive techniques, these potential risks could be mitigated. This anatomic cadaveric study serves to assess the safety of percutaneous endoscopically assisted calcaneal osteotomy (PECO) compared to a traditional open osteotomy technique. Methods: Anatomic safety of PECO was assessed using 8 fresh-frozen cadaver below-knee specimens. Lateral calcaneal nerve (LCN) damage was primarily noted and then secondly compared to a potential open surgical incision approach. Results: Only 1 of 11 LCN branches (n = 8 limbs) was transected using PECO, compared to up to 8 of 10 LCN branches (n = 6 limbs) that potentially would have been injured during open surgery. Conclusions: Percutaneous endoscopically assisted calcaneal osteotomy is a minimally invasive technique that had fewer nerve injuries in this cadaveric model than traditional open surgery. Clinical Relevance: Percutaneous endoscopically assisted calcaneal osteotomy due to its less invasive nature may result in fewer neurovascular injuries relative to an open procedure.